KOMUNIKASI PEMBANGUNAN DESA SINDANGSARI DALAM MENINGKATKAN PARTISIPASI SOSIAL MASYARAKAT - Saputra, Anggi; ., Sukarelawati; ., Agustini (JURNAL KOMUNIKATIO, 2020)
ABSTRACTThe main problem is aimed at knowing communication of Sindangsari village development in increasing social participation, rural development communication is a bridge of village and community apparatuses, opinion leaders who initiate development have an important role in planning, arranging, and choosing the right media to improve community participation in carrying out social activities. descriptive qualitative method with a phenomenological approach using observation, interview, document and literature study data collection techniques. The results of the study show that the communication development of the Sindangsari village emphasizes the importance of social aspects regardless of social status, different cultural cultures. Â Conclusion of village communication Sindangsari optimizing the smartphone and the internet through social media such as what'sapp, facebook, and instagram. In addition, in increasing social participation, the community of Sindangsari village has formed a social community.Keywords : development communication, increased participation,Â  social community, village